1975
DOI: 10.1073/pnas.72.10.4066
|View full text |Cite
|
Sign up to set email alerts
|

Induction by alkylating agents of sister chromatid exchanges and chromatid breaks in Fanconi's anemia.

Abstract: Sister chromatid exchanges, which may reflect chromosome repair in response to certain types of DNA damage, provide a means of investigating the increased chromosome fragility characteristic of Fanconi's anemia. By a recently developed technique using 33258 Hoechst and 5-bromodeoxyuridine, it was observed that the baseline frequency of sister chromatid exchanges in phytohemagglutinin-stimulated lymphocytes from four males with Fanconi's anemia differed little from that of normal lymphocytes. However, addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0
3

Year Published

1976
1976
1987
1987

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(50 citation statements)
references
References 32 publications
1
46
0
3
Order By: Relevance
“…In order to characterize the specificity of the effect of MMC on Fanconi's anemia cells, additional experiments were performed using EMS. This agent, unlike MMC, is not capable of causing appreciable DNA crosslinks and is not especially toxic to cells from patients with Fanconi's anemia (20,29). In contrast to MMC, EMS, at concentrations sufficient to more than double the sister chromatid exchange frequency in normal cells, did not effect a differential accumulation of Fanconi's anemia cells in late S or Gn + M ( Table 6).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In order to characterize the specificity of the effect of MMC on Fanconi's anemia cells, additional experiments were performed using EMS. This agent, unlike MMC, is not capable of causing appreciable DNA crosslinks and is not especially toxic to cells from patients with Fanconi's anemia (20,29). In contrast to MMC, EMS, at concentrations sufficient to more than double the sister chromatid exchange frequency in normal cells, did not effect a differential accumulation of Fanconi's anemia cells in late S or Gn + M ( Table 6).…”
Section: Resultsmentioning
confidence: 96%
“…(20). Defective sister chromatid exchange induction by mitomycin C in lymphocytes, but not fibroblasts, was observed under some conditions (29,31), that included the presence of FUdR and dC, but was not observed in cells from some patients treated by slightly different protocols (6, 35). If fibroblasts were exposed to a brief pulse of mitomycin C , those from patients with Fanconi's anemia actually ex-hibited a greater increment in SCEs than did normal cells Procedures based on metaphase chromosome analysis are compromised by the paucity of metaphase cells in cultures of FA cells (51), accentuated by exposure to mitomycin (17).…”
Section: Discussionmentioning
confidence: 99%
“…In Fanconi anemia, on the other hand, exchanges of both symmetrical and asymmetrical types preferentially involve nonhomologous chromosomes. In addition, Bloom syndrome, but not Fanconi anemia, exhibits a strikingly high frequency of sister-chromatid exchange (4,5). The existence of characteristic cytological phenotypes associated with specific genetic defects makes these studies promising not only as an aid to understanding the mechanisms of formation of chromosome aberrations, but also for inferring the role of wild-type alleles at these loci in DNA metabolism.…”
mentioning
confidence: 99%
“…For FA, additional clinical symptoms include pancytopenia with elevated levels of fetal hemoglobin, abnormal "cafe au lait"-type skin pigmentation, and stunted growth (2). Evidence for a defect in the repair of interstrand DNA crosslinks formed by the bifunctional, DNA-damaging agents mitomycin C and psoralen plus light has been presented, but the deficiency has not yet been characterized in molecular terms (3)(4)(5)(6). Some observations suggest a deficiency of FA cells in repairing DNA damage induced by monofunctional agents such as ethylmethanesulfonate (6) and decarbamoyl-mitomycin C (5).…”
mentioning
confidence: 99%
“…Evidence for a defect in the repair of interstrand DNA crosslinks formed by the bifunctional, DNA-damaging agents mitomycin C and psoralen plus light has been presented, but the deficiency has not yet been characterized in molecular terms (3)(4)(5)(6). Some observations suggest a deficiency of FA cells in repairing DNA damage induced by monofunctional agents such as ethylmethanesulfonate (6) and decarbamoyl-mitomycin C (5). It has also been reported that the exonucleolytic degradation step in the excision repair of thymine-photodimers may be deficient in skin fibroblasts from a patient with FA after exposure to relatively high doses of ultraviolet light (7).…”
mentioning
confidence: 99%